Dynamic niches in the origination and differentiation of haematopoietic stem cells - Wang, Leo D. (2011)
Haematopoietic stem cells (HSCs) are multipotent, self-renewing progenitors that generate all mature blood cells. HSC function is tightly controlled to maintain haematopoietic homeostasis, and this regulation relies on specialized cells and factors that constitute the haematopoietic ‘niche’, or microenvironment. Recent discoveries, aided in part by technological advances in in vivo imaging, have engendered a new appreciation for the dynamic nature of the niche, identifying novel cellular and acellular niche components and uncovering fluctuations in the relative importance of these components over time. These new insights significantly improve our understanding of haematopoiesis and raise fundamental questions about what truly constitutes a stem cell niche.